Association of exposure to urinary and blood heavy metals with visual disability among U.S. adults in NHANES 2013–2018 - Lingyu Dai; Qian Zhou; Yu Gao; Guannan Su; Qingyan Jiang; Lan Xia; Peizeng Yang (Frontiers in Public Health)
BackgroundHeavy metals exposure has been widely referred to as a risk factor for human health. However, studies on the potential impact of heavy metals on visual disability are limited. Herein, this study aims to investigate the associations of urinary and blood heavy metals with visual disability in adults.MethodsA total of 4,284 eligible participants in the 2013–2018 National Health and Nutrition Examination Survey (NHANES) were enrolled in our cross-sectional study. The urinary barium (Ba), cadmium (Cd), cesium (Cs), cobalt (Co), molybdenum (Mo), lead (Pb), antimony (Sb), thallium (Tl), tin (Sn), tungsten (Tu), and mercury (Hg) and blood Pb, Cd, and Hg were included for analysis. We used multivariate logistic regression, weighted quantile sum (WQS) regression, quantile-based gcomputation (qgcomp) regression, and Bayesian kernel machine regression (BKMR) to assess the mixed-metal effect on visual disability. The subgroup analysis was stratified by age.ResultsIn the single metal exposure model, the risk of visual disability increased by 39.2%, 22.6%, 25.6%, and 17.9% for each unit increase in urinary Cd, Pb, Sn, and Tu, respectively (all p < 0.05). Meanwhile, the risk of visual disability increased by 40.6% and 22.7% per unit increase in blood Ln-Pb and Ln-Cd, respectively (p = 0.034 and 0.018). In mixed metal effect analysis, WQS, qgcomp, and BKMR models consistently demonstrated a positive association between blood and urine metal co-exposure and visual disability. Furthermore, we found that Cd and Pb were the top-weighted metals responsible for the overall effect. However, these associations were not pronounced in the older adults.ConclusionsOur findings suggested that Cd, Pb, Sn, and Tu were identified as independent risk factors for visual disability. Furthermore, exposure to mixed metals could increase the risk of visual disability, to which Cd and Pb were the greatest contributors.